2018
DOI: 10.18273/revsal.v50n4-2018008
|View full text |Cite
|
Sign up to set email alerts
|

Actitudes y prácticas sexuales relacionadas con VIH/SIDA

Abstract: Forma de citar: Fernández-Silva CA, Sánchez-Martínez DE. Actitudes y prácticas sexuales relacionadas con VIH/SIDA. Rev

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
2
0
2
Order By: Relevance
“…The results of this study corroborate the results of the national study done about the same topic (Santos et al, 2016) and, in the same way as in international studies, the majority of university students was sexually active (Fernández-Silva & Sánchez-Martínez, 2018;Kebede et al, 2018;Leon-Larios & Macías-Seda, 2017;Mavhandu-Mudzusi & Asgedom, 2016;Shapiro et al, 1999;Spindola et al, 2019;Villafañe-Ferrer & González-Navarro, 2017) Generally, potentially risky sexual behaviors were reported by 82.2% of sexually active university students. This high level of prevalence of risky sexual behaviors is corroborated by the findings of recent studies carried out with students of Higher Education (Sherab et al, 2019;Yang et al, 2019), although a systematic review of the literature with Ethiopian university students estimates a prevalence ranged from 23.3% to 60.9% (Amare et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study corroborate the results of the national study done about the same topic (Santos et al, 2016) and, in the same way as in international studies, the majority of university students was sexually active (Fernández-Silva & Sánchez-Martínez, 2018;Kebede et al, 2018;Leon-Larios & Macías-Seda, 2017;Mavhandu-Mudzusi & Asgedom, 2016;Shapiro et al, 1999;Spindola et al, 2019;Villafañe-Ferrer & González-Navarro, 2017) Generally, potentially risky sexual behaviors were reported by 82.2% of sexually active university students. This high level of prevalence of risky sexual behaviors is corroborated by the findings of recent studies carried out with students of Higher Education (Sherab et al, 2019;Yang et al, 2019), although a systematic review of the literature with Ethiopian university students estimates a prevalence ranged from 23.3% to 60.9% (Amare et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…The average scores attributed to the perception of STIs among male students was higher than those attributed to female ones (Evcili & Golbasi, 2017;Fernández-Silva & Sánchez-Martínez, 2018;Leon-Larios & Macías-Seda, 2017), showing perceptions considered to be more unfavorable towards these infections.…”
Section: Sexual Knowledge and Attitudes And Sexual Risk Behaviours Am...mentioning
confidence: 80%
“…En la muestra estudiada, la proporción de personas que usaron constantemente condón es inferior a lo reportado en datos nacionales ministeriales 17 y en otras muestras de estudiantes universitarios latinoamericanos 14,18 , ya que en este último caso las cifras son cercanas al 30%. Por lo general, el uso constante de condón en estudiantes universitarios es heterogéneo [19][20][21] , con un predominio claro de prácticas sexuales de riesgo 21 . Sin embargo, las fuentes no suelen especificar la frecuencia del uso de condón según el tipo de relación sexual, por lo que sus resultados podrían ser poco específicos.…”
Section: Discussionunclassified
“…Algunas barreras para el uso de condón informadas por los estudios publicados son tener relaciones monógamas, falta de experiencia o fracaso al utilizarlo, vergüenza al comprarlos, consumir alcohol u otras drogas y la creencia acerca de la pérdida de placer o espontaneidad; no obstante, la mayor barrera sería la baja percepción de riesgo respecto de las ITS 18,19 . Otros factores individuales asociados al bajo uso de preservativo son la sensación de "invulnerabilidad" característica de esta etapa del ciclo vital 21,27 . Contrariamente, algunas investigaciones demuestran que la percepción de autoeficacia y la asertividad sexual incrementan el uso de condón en población joven 28 .…”
Section: Discussionunclassified
“…The sexual behaviour of young people therefore constitutes a major risk factor in contracting HIV/AIDS and other sexually transmitted diseases. Inconsistent use of condoms, a high number of different sexual partners, having sex after drinking alcohol and the low frequency of HIV testing are the most frequent risk behaviours reported in international research (Castro & Santos-Iglesias, 2016;Cortés Alfaro, García Roche, & Ochoa Soto, 2015;Fernández-Silva & Sánchez-Martínez, 2018;Folasayo et al, 2017;Xu et al, 2019;Mavhandu-Mudzusi & Asgedom, 2016;Othieno, Okoth, Peltzer, Pengpid & Malla, 2015;Thomas, Yarandi, Dalmida, Frados & Klienert, 2015). Previous studies showed that Spanish young people do not use condoms consistently (Bagmato, Jenaro, Flores & Guzmán, 2014;Ballester, Gil, Jiménez & Ruiz, 2009;Castro & Santos-Iglesias, 2016).…”
Section: Introductionmentioning
confidence: 99%